Factors associated with feeding problems in children with cerebral palsy: A cross-sectional study from Indonesia - Maulidia, Dwi S.; Sembiring, Tiangsa; Dimyati, Yazid; Tanjung, Ika CD.; Wahyuni, Arlinda S.; Pratita, Winra; Nasution, Halida R.; Alharbi, Olayan; Pasaribu, Ayodhia P. (Narra X, 2024)
Children with cerebral palsy are at high risk for feeding difficulties and malnutrition due to motor impairments and associated conditions. The aim of this study was to evaluate the prevalence and types of feeding problems and their association with malnutrition in children with cerebral palsy. A cross-sectional study was conducted involving 54 children under five years old with cerebral palsy. Participants were classified into spastic cerebral palsy subtypes such as quadriplegic, hemiplegic, diplegic, or triplegic. Feeding problems were categorized as inappropriate feeding practices, reduced food intake, parental misperception, and food preferences using the Pediatric Symptom Checklist-17. Nutritional status was assessed using weight-for-age percentiles based on WHO growth charts. History of constipation and dysphagia were also recorded. Data analysis included Chi-square and Mann-Whitney U tests. Among the participants, 38.9% had hemiplegia, 33.3% diplegia, and 25.9% quadriplegia. Feeding problems were prevalent, with inappropriate feeding practices being the most common (70.4%). Malnutrition was identified in 59.3% of the children. However, no significant associations were observed between CP subtype or demographic variables and the types of feeding problems. Similarly, the type of feeding problem was not significantly associated with malnutrition. Constipation and dysphagia were reported in 31.5% and 37.0% of participants, respectively, and were significantly associated with nutritional status (p<0.001). In conclusion, feeding problems and malnutrition are common in children with cerebral palsy, with inappropriate feeding practices being the most prevalent issue. Although no significant associations were found between CP subtypes or the types of feeding problems and malnutrition, the findings emphasize the multifactorial nature of feeding challenges.